Overexpression of ANXA1 in Penile Carcinomas Positive for High-Risk HPVs - Calmon, Marilia Freitas [UNESP]; Mota, Mânlio Tasso de Oliveira [UNESP]; Babeto, Erica [UNESP]; Candido, Natália Maria [UNESP]; Girol, Ana Paula [UNESP]; Mendiburu, Carlos Fabian; Bonilha, Jane Lopes; Silvestre, Rodrigo Vellasco Duarte; Rosa, Bruno Miziara; Thomé, Jorge Alberto; Medeiros, Gustavo Hernandez Américo; Soares, Fernando Augusto; et al. (Public Library of Science (PLoS), 2013)
The incidence of penile cancer varies between populations but is rare in developed nations. Penile cancer is associated with a number of established risk factors and associated diseases including phimosis with chronic inflammation, human papillomavirus (HPV) infection, poor hygiene and smoking. The objective of this study was to identify genes related to this type of cancer. The detection of HPV was analyzed in 47 penile squamous cell carcinoma samples. HPV DNA was detected in 48.9% of penile squamous cell carcinoma cases. High-risk HPV were present in 42.5% of cases and low-risk HPV were detected in 10.6% of penile squamous cell carcinomas. The RaSH approach identified differential expression of Annexin A1 (ANXA1), p16, RPL6, PBEF1 and KIAA1033 in high-risk HPV positive penile carcinoma; ANXA1 and p16 were overexpressed in penile squamous cells positive for high-risk HPVs compared to normal penile samples by qPCR. ANXA1 and p16 proteins were significantly more expressed in the cells from high-risk HPV-positive penile carcinoma as compared to HPV-negative tumors (p<0.0001) independently of the subtype of the carcinoma. Overexpression of ANXA1 might be mediated by HPV E6 in penile squamous cell carcinoma of patients with high-risk HPVs, suggesting that this gene plays an important role in penile cancer. © 2013 Calmon et al.
Keywords: lipocortin 1; protein p16; virus DNA; adult; aged; ANXA1 gene; clinical article; controlled study; gene; gene overexpression; high risk patient; human; human tissue; KIAA1033 gene; male; nonhuman; p16 gene; papillomavirus infection; PBEF1 gene; penile squamous cell carcinoma; penis carcinoma; protein expression; RPL6 gene; squamous cell carcinoma; tumor classification; Wart virus; Adult; Aged; Aged, 80 and over; Annexin A1; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Genotype; Humans; Immunohistochemistry; Male; Middle Aged; Nucleic Acid Hybridization; Papillomaviridae; Papillomavirus Infections; Penile Neoplasms; Polymerase Chain Reaction; Reproducibility of Results; Risk Factors; Human papillomavirus